Stress-induced effects in light scattering by plasmons in p-type germanium - Poroshin, V.N.; Gaydar, A.V.; Abramov, A.A.; Tulupenko, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Infrared light scattering by plasmons in p-Ge has been studied under uniaxial stress along the [110] axis with polarization of incident light parallel to the stress direction. It is found that the deformation of the crystal results in an increase of the plasma frequency and lowering the asymmetry of the line by plasma scattering. These effects are explained by taking into account the change of contribution to the dielectric constant caused by the intra- and intersubband transitions as a consequence of variation of the energy band of p-Ge related with deformation.